Effect of capital structure on profitability performance of wood-based companies listed in Bursa Malaysia - Chanmontri, Siravidh (2019)
This study investigates the relationship between capital structure and profitability performance of wood-based companies listed in Bursa Malaysia from the year 2013 to 2017. This research employed current ratio (CR) and natural log of total debt (LNTD) as indicator of capital structure or independent variables. For profitability performance, the dependant variables earnings before interests and taxes (EBIT) and return on capital employed (ROCE) were used as indicators. Pearson correlation analysis was used to find whether there is an association between dependant and independent variables while multiple linear regression was used to test the strength of the association between dependant and independent variables. The results indicate a positive relationship between capital structure indicator of CR and LNTD to profitability performance indicators of EBIT. Other than that, a positive relationship also exists between capital structure indicators for both CR and LNTD with profitability performance indicator of ROCE. In short, the findings of this research suggest that debt financing in capital structure leads to a higher profit for wood-based companies listed in Bursa Malaysia. The results of this research could be useful to financial managers of wood-based companies listed in Bursa Malaysia.